Exports and firm characteristics in German manufacturing industries - Joachim Wagner (Institute for the Study of Labor (IZA), 2010)
Reliable information on the characteristics of exporting and non-exporting firms is important to guide theorists and policy makers in an evidence based way. This holds true especially for Germany, a leading actor on the world markets for goods and services. This paper makes three contributions towards this aim: (1) It provides a synopsis and a critical assessment of 51 empirical studies on exports and firm characteristics that use data for German establishments or enterprises, arguing that this literature is not suited to extract the stylized facts needed. (2) It uses recently released rich high quality data for a large representative panel of enterprises from German manufacturing industries to investigate the links between firm characteristics and export activities, demonstrating the decisive role of human capital intensity for exporting. (3) It links these findings to the recent literature from the new new trade theory on international activities of heterogeneous firms that emphasises the role of productivity for exporting. It shows that productivity is important for exporting as is hypothesized in the formal theoretical models, but that contrary to the assumption made in these models productivity is not (only) the result from a random draw from the productivity distribution - it is strongly positively related to human capital intensity.
Keywords: F14; 330; exports; firm characteristics; Germany